A right to north: considering territory in the 21st century - Hildebrandt, Lorena, author; McIvor, David, advisor; Velasco, Marcela, committee member; Sagás, Ernesto, committee member (Colorado State University. Libraries, 2022)
Humanity has a profound migratory past, incited and shaped substantially by climate change over time, spanning from the earliest humans to the current day. As greenhouse gas emissions rise to levels unprecedented for human history, climatic changes are certainly never more relevant to human movement and settlement. Yet even while greenhouse gas emissions and climatic changes move freely across global space, the movement of people in the 21st century is deeply restricted and, in some cases, prohibited by state territory. Territory's rights, and its associated technologies and practices, confine and restrict, even as the world warms. This project writes against state territory in its current political form utilized by democracies in the global North. It considers territory's history, definition and defenses, the paradox it creates for democratic consent, and its power and subjects. The final chapter of the project imagines resistance to territory and spaces of creolized alterity, articulating a right to both movement and North.